Unconventional fiscal policy - Francesco D'Acunto; Daniel Hoang; Michael Weber (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2018)
Macroeconomists often prefer monetary policy to fiscal policy as a tool to stabilize business cycles. Fiscal policy is typically only effective with a lag, and results in permanent deficits with higher nominal interest rates and distortionary taxes. In addition, a high marginal propensity to save out of temporary tax cuts might result in low fiscal multipliers with empirical estimates often below 1 (see Ramey (2011b) and Barro and Redlick (2011)). The zero lower bound on nominal interest rates, however, constrains the effectiveness of monetary policy during liquidity traps. Large stocks of sovereign debt limit the scope of fiscal stimulus, and inflated central bank balance sheets constrain asset-purchase programs as forms of unconventional monetary policy. The unclear effectiveness of several measures of monetary policy - both conventional and unconventional - after the 2008-2009 Financial Crisis calls for alternative mechanisms to increase aggregate demand and hence promote growth. This issue is especially relevant for several major developed economies that, years after the end of the Great Recession in the United States, are still experiencing sluggish growth. In particular, southern European countries are still facing the contractionary effects of the austerity measures they implemented to abate their debt-to-GDP ratios during the Euro sovereign-debt crisis. Many economists argue structural reforms are necessary to improve the competitiveness of these countries in the long run, but promoting a short-run increase in aggregate demand to jump start the economy is also a compelling objective for policy makers. The conundrum the Euro area has faced since the start of the Great Recession is to generate inflation and ultimately stimulate consumption and economic growth in a setting in which traditional monetary policy measures were not viable and governments could not generate growth with fiscal stimulus because of their large debt-to-GDP ratios. This challenge was so compelling that in his Marjolin lecture on February 4, 2016, the president of the European Central Bank, Mario Draghi, asserted that "there are forces in the global economy that are conspiring to hold inflation down." (Draghi, 2016).
urn:nbn:de:swb:90-798859
Keywords: 330